Influence of the HPV-16 on IL-10 intralesional productionin immunogenetically responsive women carrying HIV-1 infection - Fernandes, Ana Paula M.; Gonçalves, Maria Alice G.; Simões, Renata T.; Quintana, Silvana Maria; Duarte, Geraldo; Donadi, Eduardo A. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: Infection with human papillomavirus 16 (HPV 16) is considered to be the major risk factor for cervical cancer development. Cytokines playan important role in the defense against viral infection. Such differences may be attributed to genetically determined molecular mechanisms includingvariations in transcription, translation and secretion pathways Genetically determined, has been predominance of Th1 polarization, associated with the clea-rance of HPV infection or, in contrast, with immunosuppressive cytokines associated with persistence of HPV infection and progression to cervical lesions,as interleukine 10 (L-10). Furthermore, the human immunodeficiency virus type 1 (HIV-1) infection is co morbidity to cervical lesions development.Objective:to further evaluate the HPV16 infection influence on immunogenetic factors associated with IL-10 immunoinibitory cytokine production levelsin women presenting with HIV infection and squamous intraepithelial lesions. Method: ross-sectional study (n = 42 cervical biopsies from 22 HIV - and20 HIV +). Cytokine polymorphism, and HPV detection and typing were performed using amplified DNA hybridized with sequence specific primers, andcytokine intralesional levels were detected using ELISA. Result:independence of HIV infection, women HPV16 infected presenting with low productionallele associated with IL-10 exhibited increased intralesional levels of IL-10 compared to HPV16 negative women (p = 0,01). Conclusion:presence ofHPV16 infection, irrespective of co morbidity of the HIV-1 infection, may predispose to cervical lesion installation and progression, due the presence ofpermissive response, with increased IL-10 levels, inclusive among women with immunogenetically responsive to installation and progression cervicallesions to cervical cancer.